Investigating Energy Efficiency of Mobile Ad-hoc Network Routing Protocols (Informatica, 2022)
Mobile Ad-hoc Network (MANET) is a wireless network that comes with a few routing protocols which havevaried mechanisms. Studies show that routing operations consume energy while current research focuses more on MANET routing protocol operation and its performance evaluation, the required energy for successful routing operations equally demands quality attention of researchers. Hence, the need to expand the scope of study on MANET routing protocols to the neglected area of studies. To bridge the research gap between MANET routing protocols and energy consumption, this paper used residual energy to analyze routing protocols’ energy efficiency as a metric to analyze selected routing protocols; Destination Sequence Distance Vector (DSDV) and Ad-hoc On-demand Distance Vector (AODV) via simulation. It also compared the amount of energy required to transmit the data packets to their destinations in DSDV and AODV. Results, in terms of energy efficiency, indicated that AODV was better than DSDV because it consumed less energy for its successful routing operations